Diagnosis and management of vascular injuries after joint arthroplasty - Sarinya Meknarit; John C. Motta; Eileen de Grandis; W. Anthony Lee (Annals of Vascular Surgery - Brief Reports and Innovations, 2023)
Background: This combined single-center retrospective case series and systematic review aims to report the clinical presentation, diagnosis, management, and outcome of intraoperative vascular injuries associated with elective joint arthroplasty. Methods: A retrospective review of electronic medical records was conducted of all patients who sustained a vascular injury after elective joint arthroplasty at a single regional referral center from 2014 to 2022. Ten patients were identified and included in our case series. A systematic review of the literature was also conducted using the PubMed database, from which 992 articles were identified and 23 English-language publications (31 cases) were selected for full-text review. Results: Total of 41 cases combined from our series and those reported in the literature were reviewed. Majority of the procedures were comprised of total knee arthroplasty (66%) and total hip arthroplasty (22%). Twenty-six (63.4%) vascular injuries were detected either intraoperatively or within 24 h postoperatively. Definitive diagnosis was made with angiography in 83% of cases. Vascular injuries mostly consisted of transection/laceration/rupture (46%) and pseudoaneurysm (44%). All of the interventions required either endovascular (71%) and/or surgical (29%) procedures. Conclusions: Total knee arthroplasty is the most common procedure associated with serious iatrogenic vascular injury. Timely recognition, diagnosis, and immediate intervention can restore limb perfusion and mitigate the risk of loss of limb or function.